Pengaruh Posisi Biji Pada Polong Terhadap Perkecambahan Benih Beberapa Varietas Lokal Bengkuang (Pachyrizus erosus L.) - Krisnawati, Ayda; Adie, M. Muchlish (Perhimpunan Biologi Indonesia, 2018)
ABSTRACTThe yam bean seeds are formed in relatively long pods containing between 6-12 seeds/pod. A total of six local yam bean accessions from Indonesia was studied for its seed position in pod related to seed viability and vigor. Field research was carried out in Malang (Indonesia) from May - October 2016. Twenty five matured pods were detached from each accession. Each pod was divided into three parts, i.e. base, middle, and tip part. The seeds of each part are mixed and taken as many as 20 seeds for germinating. The design was a completely randomized design with two factors and repeated three times. The first factor was three seed positions (base, middle, and tip) and the second factor was six accessions of Indonesian local yam bean. The analysis of variance showed that seed position had significant effect on individual seed weight, leaf length, leaf width, leaf shape index, seedling dry weight, and root dry weight. Seeds derived from the midde of the pods produce the highest leaf length, leaf width, leaf shape index, seedling dry weight, and root dry weight. The parameters of seed viability and vigor were not affected by the seed position in the pods. Therefore, the seed viability and vigor of yam bean plant in the field can be produced from the seeds derived from the tip, middle and base of the pod. Keywords: seed position, viability, vigor, yam bean